Kualifikasi Kompetensi Calon Wartawan Era Digital di Indonesia - F.X. Lilik Dwi Mardjianto (Universitas Multimedia Nusantara, 2018)
Journalism is growing rapidly in this era of multimedia. Along with the development of digital and multimedia technology, competencies of journalists are also shifting. This research implements FGD method to identify emerging journalism competencies that have to be mastered by multimedia journalists. The participants of the FGD were chosen to fulfill specific consideration: they should be journalists working in different areas (journalists, freelance journalists, and entrepreneur journalists). This is so important that this study could comprehensively elaborate new competencies that have to be mastered by journalists. Despite the need to master basic journalism skills, this study reveals that multimedia journalists are also required to have content distribution and media entrepreneurship skills. Keywords: competencies, journalism, journalists, digital